FRI0374 Milder clinical presentation of lupus nephritis and improved renal survival during the last 50 years: a multicentric study. (12th June 2018) - Gatto, M.; Moroni, G.; Raffiotta, F.; Vercelloni, P.G.; Quaglini, S.; Sacchi, L.; Gainfreda, D.; Vaglio, A.; Sinico, R.A.; Doria, A.
Abstract : Background: Lupus nephritis (LN) presentation changed over time following earlier diagnosis and treatment. Objectives: To evaluate changes in LN clinical and histological presentation in the last 5 decades. Methods: This is a retrospective multicentric study on prospectively collected data in four Italian hospital centres. Patients diagnosed between 1970 and 2016 were recruited provided they had a biopsy-proven LN that was retrospectively reclassified according to the ISN/RPS classification criteria. Follow-up was subdivided into three periods (P) based on the year of LN diagnosis: P1:1970–1895; P2:1986–2000; P3:2001–2016. Predictors of patient and renal survival were investigated by univariate and multivariate analysis; survival curves were compared by log-rank test. Clinical pictures at presentation included isolated urinary abnormalities, nephrotic syndrome, nephritic syndrome, rapidly progressive renal failure. Outcome at last observation was defined as complete renal remission or partial renal remission, or poor renal outcome, including chronic kidney disease (CKD) or end stage renal disease (ESRD). Results: 499 patients were included (85.6% females) with a median follow-up of 10.6 years (IQR 4–18). We observed an increase in both age at diagnosis of LN (P1 28.4±10.4; P2 29±11.5; P3 34.4±13.3 years) and disease duration before LN diagnosis (P1 1.3±1.3; P2 2.6±4.5; P3 4.6±6.3 years) from 1970 to 2016 (p<0.001 for both). At clinical presentation, renal insufficiency and acute nephritic syndrome became less common (P1 14.2%; P2 3.9% ; P3 3.4% and P1 29%, P2 20.3%; P3 12.4%, respectively, p<0.0001) while isolated urinary abnormalities became significantly more prevalent from P1 to P3 (P1 26.4%; P2 38%; P3 48.9%; p<0.0001). Outcome was available in 95.8% of patients. Frequency of partial and complete renal remission progressively increased (P1 6.9%; P2 28%; P3 32% and P1 49.6%; P248% ; P3 58.5%; p<0.001 and p=0.01, respectively) while CKD, ESRD and death decreased (P1 7.9%; P2 8.5%; P3 4.5% ; P1 24.8% P2 9%; P3 1.3%; P1 19.8%; P2 5.9%; P3 3.6%, respectively. p<0.001 for all). Survival without ESRD at 10 and at 20 years was 87% and 80% in P1, 94% and 90% in P2% and 99% in P3 (p=0.0019). Induction therapy with immunosuppressants was more frequently performed over time (P1 71%; P2 82%; P3 94.6%, p<0.0001) and use of MMF significantly increased both as induction and maintenance treatment (P1 0, P2 2.7%; P3. 33.8% and P1 1%; P2 15%; P3 54.8%, respectively; p<0.0001). At multivariate analysis, logarithm of serum creatinine (RR:2.72), male gender (RR:3.34), activity index (RR:1.1), chronicity index (RR:1.29), arterial hypertension (RR:5.95), and lack of maintenance immunosuppressive therapy (RR:3.04) predicted ESRD. No significant changes in histological classes or active lesions at the time of renal biopsy were observed, while chronicity index significantly decreased from P1 to P3 (p=0.023). Conclusions: The clinical presentation of LN apparently became less severe in the last decades, likely due to earlier diagnosis and proper treatment, leading to an improved renal survival. Disclosure of Interest: None declared